Level of entrepreneurship in the management of universities in the Tacna and Moquegua regions. - Mendoza Blanco, Werner (2013)
Objetive: The general objective was to compare the level  of entrepreneurship in the management of private  universities from thecities of Tacna and Moquegua, and  the general hypothesis was: the UPT has greater level of  entrepreneurship in the university managementthan the  UJCM.  Theresults of the survey showed that the managers of the  UPT have greater percentage of correct answers on the  level of knowledge about entrepreneurship, planning,  presence of enterprising profile, knowledge about  infrastructures, teaching and learning and economic  resources than UJCM managers.  Method: Theinvestigation is a retrospective-comparative  and unique variable study. It included a survey of 41  questions oriented to managers from Universidad José  Carlos Mariátegui (UJCM) in Moquegua and from  Universidad Privada de Tacna (UPT) in Tacna. The survey  had 6 parts orindicators.  Result: The results were subjected to Student's T-test  analysis for independent averages with a significance  level of5%.  Conclusion: UPT obtained a statistically significant  greater level of entrepreneurship in the university  management than the UJCM